MRI Study on the Distance between the Distal Radius and the Flexor and Extensor Tendons: Is There Any Room for Error/Hardware? - Bergsma, Minke; Board, Jemara; Doornberg, Job N.; Sierevelt, Inger; Rickman, Mark; Jaarsma, Ruurd L.; Obdeijn, Miryam C. (Journal of Wrist Surgery, 2019)
Purpose This study aims to quantify the distances between the cortex of the distal radius and flexor and extensor tendons.Methods We analyzed 50 magnetic resonance images (MRI) of intact wrist without pathology. The distances between the volar cortex and the flexor pollicis longs (FPL), index flexor digitorum profunduns (FDPi), flexor digitorum profundus (FDP), and flexor digitorum superficialis (FDS) were measured at the level of the watershed line and 3- and 6-mm proximal to this level. The distances between the dorsal cortex and the extensor carpi radialis longus (ECRL), extensor carpi radialis brevis (ECRB), extensor pollicis longus (EPL), extensor indicis proprius (EIP), and the extensor digitorum communis (EDC) were measured at the level of Lister's tubercle and 5-mm distal to this level. Analysis was descriptive.Results At the watershed line, the FPL, FDPi, FDP, and FDS were located at an average of 3.1, 2.4, 3.6, and 5.1 mm, respectively, volar to the volar cortex. The distances of the FDP and FDS increased at 3-mm proximal to the watershed line and increased for all four tendons at 6-mm proximal to the watershed line. Dorsally, at Listers' tubercle the ECRL, ECRB, EPL, EIP, and EDC were identified at an average of 0.7, 0.5, 0.5, 2.6, and 3.2 mm, respectively, dorsal to the dorsal cortex of the distal radius. At 5-mm more distal, these tendons were located on average 1.2, 1.0, 0.7, 1.9, and 1.8 mm, respectively, dorsal to the dorsal cortex.Conclusion On the volar side, on average there is enough room for a volar plate when staying proximal to the watershed line. On the dorsal side, there is virtually no room for protruding screws as physical anatomical space is limited to a maximum of 0.7 mm from cortex to the closest tendon (the FDP), with screw increments being 2 mm.Level of Evidence This is a Level II Study.
Keywords: flexor tendons; extensor tendons; distal radius; volar plating; MRI